Community Case Study on Trauma-Specific Treatment and Counseling for Refugee Women Exposed to Intimate Partner Violence - Pogarell, Anneke; Garthus-Niegel, Susan; Mojahed, Amera; von Verschuer, Clara; Rokyta, Ute; Kummer, Wenke; Schellong, Julia (Frontiers in Psychiatry, 2019)
Women experiencing intimate partner violence (IPV) are at high risk to suffer from severe mental health consequences, such as posttraumatic stress disorder (PTSD) and depression. Refugee women being exposed to IPV in the country of arrival are an especially vulnerable and understudied group and post migration persistent IPV should not be underestimated. Hence, research on special requirements regarding the treatment of these women is needed. We describe two individual cases from our work with refugee women suffering from PTSD symptoms who experienced IPV representing our trauma-specific therapeutic approach targeting this population. By analyzing their personal and medical history as well as their interactions with several institutions of the public sector and counseling centers, we illustrate the possibilities and limitations when helping our clients dealing with trauma-related mental health problems following the experience of IPV. Furthermore, we formulate general recommendations for providing adequate therapeutic frameworks concerning special requirements for the work with refugee women.